Clinical Reliability of Complete-Arch Fixed Prostheses Supported by Narrow-Diameter Implants to Support Complete-Arch Restorations - Claudia Lorenzi; Fabrizio Lio; Piero Papi; Vincenzo Mazzetti; Andrea Laureti; Claudio Arcuri (Applied Sciences, 2022)
The aim of this study was to evaluate the clinical application of fixed screw-retained complete-arch rehabilitations supported by four narrow-diameter implants (NDIs). The records of patients treated with complete-arch prostheses screwed onto four NDIs treated with an immediate loading protocol between 2010 and 2020 with at least 1 year of follow-up after the positioning of the definitive restoration were reviewed. The implants were placed according to the final prosthetic design and were immediately loaded. The interim prostheses were replaced after the healing period by definitive acrylic resin titanium-supported prostheses. Patients were followed to evaluate treatment success, the implant survival rate (ISR), and the prosthetic survival rate (PSR). A total of 121 NDIs were positioned in 30 patients to restore 30 complete arches (18 maxilla and 12 mandible). One implant did not achieve osseointegration, resulting in an overall ISR of 99.2%. No prosthetic or implant failures occurred during the 1 to 11 years of follow-up. Three biological and four prosthetic complications occurred, resulting in a treatment rehabilitation survival of 94.1% and a PSR of 86.7%. Despite the limitations of the present retrospective study, such as the use of one single type of dental implant and patients treated in a single rehabilitation center, complete-arch rehabilitation with fixed prostheses supported by four NDIs seems to be a reliable treatment in the medium to long term.